(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study examined the effects of balance training using a Wii Fit balance board on the balance, gait, and activities of daily living in patients with Parkinson disease. Method/Statistical Analysis: Our study included 15 patients with Parkinson disease who scored 2–3 on the Hoehn and Yahr scale and underwent occupational therapy. Participants were randomly assigned to two groups: the experimental group with 8 patients or the control group with 7 patients. All subjects in two groups received traditional occupational therapy (TOT) for 30 min/day, 3 times a week, for 8 weeks, and the participants in the experimental group additionally received a balance training using a Wii Fit (BTWF) for 30 min per session. All patients in both groups were evaluated using the Berg balance scale (BBS), the time up & go test, and the modified Barthel index. Findings: The experimental and control groups showed significant improvements in all outcome measures after intervention. In particular, the experimental group showed a more significant improvement in the BBS score than the control group. Improvements/Applications: BTWF could be effectively used to improve the balance of Parkinson’s disease patients in the clinic.